2022
DOI: 10.1002/fsn3.2803
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance and preference for brown rice—A mixed‐method qualitative study from Nepal

Abstract: Background Brown rice consumption reduces the risk of diabetes. The prevalence of diabetes is increasing in Nepal; however, dietary preference remains for white rice. This study aimed to understand the perception, enablers, barriers, and facilitators of acceptance brown rice at a worksite cafeteria. Methods We conducted a mixed‐method qualitative research among 42 employees of a hospital in central Nepal. The participants tasted and rated the qualities of five different combinations of brown and white rice on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additionally, the texture and flavor of brown rice may not be as universally appealing as those of white rice, posing difficulties for individuals with large families. Previous studies conducted in Asia, Latin America, and Africa have identified various barriers to the acceptance of brown rice, including limited awareness of its nutritional benefits, and its particular sensory attributes [29][30][31][32][33][34][35][36]. Practical constraints related to market availability, price, and cooking requirements also contribute to these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the texture and flavor of brown rice may not be as universally appealing as those of white rice, posing difficulties for individuals with large families. Previous studies conducted in Asia, Latin America, and Africa have identified various barriers to the acceptance of brown rice, including limited awareness of its nutritional benefits, and its particular sensory attributes [29][30][31][32][33][34][35][36]. Practical constraints related to market availability, price, and cooking requirements also contribute to these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the texture and flavor of brown rice may not be as universally appealing as those of white rice, posing difficulties for individuals with large families. Previous studies conducted in Asia, Latin America, and Africa have identified various barriers to the acceptance of brown rice, including limited awareness of its nutritional benefits, and its particular sensory attributes [32][33][34][35][36][37][38][39]. Practical constraints related to market availability, price, and cooking requirements also contribute to these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the research team decided and conducted a brown rice tasting experiment with 40 employees of the hospital. After tasting brown rice, the participants perception on brown rice changed positively [ 17 ].…”
Section: Methodsmentioning
confidence: 99%